Artists recreating our world with Rachmaninoff as a guide and partner - Bathurst R (AccScience Publishing, 2024)
This paper proposes that artists be at the forefront of community recovery in our post-COVID-19 world. To achieve this proposition, it delves into the early professional life of the renowned Russian composer and pianist Sergei Rachmaninoff (1873 – 1943), notably focusing on his sense of failure after the premiere of his first symphony and his subsequent recovery. It examines the importance of mentors who support professionals through early career mistakes, the significance of learning the limits of risk-taking, and the value of failure as guidance for development. Rachmaninoff’s contribution to humanity is profound, as evidenced by the enduring performance of his music in concert halls around the globe, making him an appropriate guide and partner in fulfilling the recovery agenda.
Keywords: Career development; Diplomacy; Failure; Leadership; Music; Political skill